Bio-Nanocomposite Films Based on Cellulose Nanocrystals Filled Polyvinyl Alcohol/Alginate Polymer Blend - Houssine Khalili; Mohamed Hamid Salim; Sif-eddine Jabor Tlemcani; Rachid Makhlouf; Fatima-Zahra Semlali Aouragh Hassani; Houssine Ablouh; Zineb Kassab; Mounir El Achaby (Journal of Fibers and Polymer Composites, 2022)
In this work, the Juncus plant was used as an abundant and sustainable raw material for the production of cellulose nanocrystals (CNC). Herein, cellulose nanocrystals were prepared via sulfuric acid hydrolysis exhibiting a needle-like shape morphology, with an average diameter of 6.8 ± 1.8 nm and length of 457 ± 76 nm, arising to an aspect ratio of 59. Moreover, X-ray diffraction and TGA show that the CNCs exhibit high crystallinity and good thermal property respectively compared to other sources. Further investigation was conducted by preparing novel bio-nanocomposites through the incorporation of CNCs into the polyvinyl alcohol- alginate (PVA-ALG) blend matrix. Thus, giving enhanced properties compared to the pure matrix, particularly the mechanical properties due to the good interfacial adhesion, confirmed by FTIR analysis, while maintaining good transparency at low CNCs concentration, which is required for packaging application.